Pengaruh Teknik Tegangan Tinggi Terhadap Entrasce Skin Exposure( ESE ) dan Laju Paparan Radiasi Hambur Pada Pemeriksaan Abdomen - Dhahryan, Dhahryan; Azam, M. (BERKALA FISIKA, 2009)
The measurement for influence of high voltage technique to Entrance Skin Exposure and Â Rate of Scattered Radiation Exposure on abdomen inspection have been conducted. The ESE measurement is conducted using Electrometer and Â calculated by semi empirical method, while in measurement of rate of scattered radiation exposure using survey meter at a distance of 100 cm from the object by varying data intake points and its direction of detector. The result indicates that the usage of high voltage technique yields absorbent dose of 124 mrad and radiation exposure of 339 mR. It is lower than the standard value of absorbent dose of 322.7 mrad and radiationÂ  exposure of 130,5 mR. The result of measurement is higher than calculation. In measurement of exposure of scattered radiation rate with detector position faced to object, on right side of cathode, it yields 1.03mR/hour with standard voltage and 0.32 mR/hour with high voltage technique. While in measuringÂ  exposure of scattered radiation rate and back-scattered obtained result on Aâ€™ and Câ€™ (close to anoda and side of object) and Aâ€ and Câ€ nearly same, with highest value of 1 mR/hour and 0.93 mR/hour at standard tube voltage and at high kV technique obtained lower value of 0.29mR/hour and 0.25mR/hour.